2019
DOI: 10.1002/hbm.24809
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain connectivity and male vulnerability in very preterm children

Abstract: Evidence indicates better cognitive and behavioral outcomes for females born very preterm (≤32 weeks gestation) compared to males, but the neurophysiology underlying this apparent resiliency of the female brain remains poorly understood. Here we test the hypothesis that very preterm males express more pronounced connectivity alterations as a reflection of higher male vulnerability. Resting state MEG recordings, neonatal and psychometric data were collected from 100 children at age 8 years:very preterm boys (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 57 publications
6
19
0
Order By: Relevance
“…The thalamus is a relay hub for sensory input from the periphery to the cortex; therefore, this brain region is of particular interest in understanding long‐term effects of early pain. At age 7‐8 years, we found that greater exposure to neonatal pain (especially in children born 24‐28 weeks GA) was associated with altered MEG oscillatory activity 39 , 40 , 41 , 42 which is generated in the thalamus and reflects functional thalamocortical connectivity. Recently, we established that structural thalamic growth on MRI from early life to term equivalent age is affected by greater exposure to neonatal pain, in two new independent cohorts in Vancouver and Switzerland that underwent serial MRI in the neonatal period.…”
Section: Pathways Of Long‐term “Effects” Of Pain‐related Stress In Ve...mentioning
confidence: 86%
See 3 more Smart Citations
“…The thalamus is a relay hub for sensory input from the periphery to the cortex; therefore, this brain region is of particular interest in understanding long‐term effects of early pain. At age 7‐8 years, we found that greater exposure to neonatal pain (especially in children born 24‐28 weeks GA) was associated with altered MEG oscillatory activity 39 , 40 , 41 , 42 which is generated in the thalamus and reflects functional thalamocortical connectivity. Recently, we established that structural thalamic growth on MRI from early life to term equivalent age is affected by greater exposure to neonatal pain, in two new independent cohorts in Vancouver and Switzerland that underwent serial MRI in the neonatal period.…”
Section: Pathways Of Long‐term “Effects” Of Pain‐related Stress In Ve...mentioning
confidence: 86%
“…Above and beyond neonatal clinical factors related to prematurity, Brummelte and Zwicker as post‐docs, found neonatal pain/stress was related to white matter and grey matter 34 and corticospinal tract maturation 35 in the neonatal period. In a separate cohort, Doesburg and Ranger post‐docs and Vinall a PhD student showed neonatal pain/stress predicted white matter maturity, 36 cortical thickness, 37 regional cerebellar volumes, 38 and neuronal activity 39‐42 at school age, and in turn, cognitive function and behavior. Recently, Doesburg with his students has extended this work 40,42 .…”
Section: Pathways Of Long‐term “Effects” Of Pain‐related Stress In Ve...mentioning
confidence: 98%
See 2 more Smart Citations
“…For these two participants, we selected the best matched MRI from the pool of the other 18 participants based on the mean distance between each Polhemus point and the closest point on the skull surface derived from the segmented T1 image using the Fieldtrip toolbox ( Oostenveld et al, 2011 ). The same procedure was previously successfully applied in the children cohort of similar age ( Kozhemiako et al, 2019 , 2020 ).…”
Section: Methodsmentioning
confidence: 99%